2019
DOI: 10.1136/bcr-2018-228696
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Stafford Interview for assessing perinatal bonding disorders

Abstract: Perinatal bonding disorders have been advocated by Brockington and he developed the semistructured Stafford Interview which contains a specific section to assess these disorders. To our knowledge, this is the first report on a fully described clinical case by using the interview. A 29-year-old primiparous mother gave birth to a healthy girl, but visited our clinic because of depression at one month postnatally and received pharmacotherapy. Despite improvement of her depression, at around 7 months postnatally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Though a considerable proportion of women delay the onset of affection towards their babies postpartum, most develop affection for them during the rst six months after birth [23]. However, regarding pathological anger towards the baby, Brockington [5] and the current researchers of this study [17] have reported cases of women whose anger emerges later than one month postpartum. In further research, the application of the Stafford Interview in the latter period of the postnatal year is expected to reveal another high-risk time point for mother-infant relationship disorder, in particular, pathological anger.…”
Section: Availability Of Questionnaires For Bonding Disordersmentioning
confidence: 62%
See 1 more Smart Citation
“…Though a considerable proportion of women delay the onset of affection towards their babies postpartum, most develop affection for them during the rst six months after birth [23]. However, regarding pathological anger towards the baby, Brockington [5] and the current researchers of this study [17] have reported cases of women whose anger emerges later than one month postpartum. In further research, the application of the Stafford Interview in the latter period of the postnatal year is expected to reveal another high-risk time point for mother-infant relationship disorder, in particular, pathological anger.…”
Section: Availability Of Questionnaires For Bonding Disordersmentioning
confidence: 62%
“…Brockington gave Yoshida (one of the authors of this paper) permission to translate the sixth edition of the Stafford Interview mentioned above into Japanese, and the authors of this paper completed and published the translation in 2022. Furthermore, as a section of "the mother-infant relationship" within this interview can be used to assess maternal bonding on its own, we have already reported a case of emotional rejection using this interview section in a preliminary study [17].…”
Section: Introductionmentioning
confidence: 99%
“…About 300-750 per 1000 mothers globally, suffer from postpartum blues which is resolved from a few days to a week and has some negative impacts whereas postpartum psychosis begins from four weeks postpartum and it can also lead to hospitalization; and this can have prevalence rates ranging from 0.89-2.6 per 1000 childbirths.And in postpartum depression, this can start soon after the childbirth and needs to be treated through various therapies otherwise can lead to disruption of mother-infant relationship, child development and its growth. About 5-7 children of mothers who are suffering from PPD can have the highest cognitive behavioural and related problems as compared with the children of the nondepressed mothers as this can have high prevalence rates as 100-150 per 1000 births [17,18].…”
Section: Types Of Postpartum Depression (Ppd)mentioning
confidence: 99%